Locus of Control dan Coping Stress pada Santri Pondok Pesantren - Eko Sujadi; Y Sonafist; Yuserizal Bustami (Institut Agama Islam Negeri Kerinci, Indonesia, 2020)
Locus of control (LoC) is a concept in psychology that refers to individuals' perceptions of the extent to which they believe they have control or influence over events occurring in their lives. One influencing factor on LoC is gender. Some previous literature has also demonstrated that LoC has an impact on the use of coping stress strategies. The aim of this study is to compare LoC between male and female students (santri) and to investigate its influence on coping. A cross-sectional online survey design was employed to collect data on LoC and coping. A total of 94 santri from a boarding school in Pekanbaru City participated by completing coping and Rotter's Internal-External Locus of Control (I-E Scale) research scales. The research findings confirm that there is a significant difference in locus of control between male and female santri, as well as a significant influence on the coping strategies they employ. The findings of this research have important implications for prevention and alleviation programs for santri coping with stress. The provision of guidance and counseling services for all santri is crucial. Additionally, the involvement of parents and peers is deemed effective in shaping resilient santri when facing psychological pressure.